PERAN KECERDASAN BUATAN DALAM MEMBENTUK BUDAYA AKADEMIK DISKUSI KRITIS PADA MAHASISWA PENDIDIKAN SOSIOLOGI UNIVERSITAS MATARAM - Made Widia Cindani; Nanda Haerani; M. Sururi Hafizin; Maliki; M. Adittya; Sumitro; Rakhmat Nur Adhi (STKIP Subang, 2026)
The development of artificial intelligence (AI) has brought changes to various student academic activities, including the learning and discussion process in higher education. However, the increasing use of AI raises issues regarding how this technology affects academic culture and students' critical thinking abilities. This study aims to analyze the role of AI in forming an academic culture of critical discussion among students in the Sociology Education Study Program at Mataram University and identify the impact of its use in academic activities. The study was carried out using a qualitative phenomenological approach to understand students' experiences in utilizing AI as part of the learning process. Data was obtained through in-depth interviews, participant observation and documentation. The results of the study show that AI is used by students to understand material, find references, summarize information, and help prepare academic assignments. In addition, AI has a double impact on critical thinking abilities. On the one hand, AI helps broaden horizons, enrich perspectives, and increase student readiness in academic discussions. On the other hand, the passive and unverified use of AI has the potential to reduce analytical abilities, originality of ideas and quality of discussions. The results of the study also show that students are aware that AI should function as a tool to support thinking processes, not as a substitute for intellectual abilities. Therefore, it is necessary to strengthen critical digital literacy and use AI ethically and responsibly so that this technology can support the formation of a critical, reflective and quality academic culture.